Elbasvir and grazoprevir for hepatitis C virus genotype 1 infection in people with recent injecting drug use (DARLO‐C): An open‐label, single‐arm, phase 4, multicentre trial. Issue 2 (15th March 2020) - Grebely, Jason; Read, Phillip; Cunningham, Evan B.; Weltman, Martin; Matthews, Gail V.; Dunlop, Adrian; Montebello, Mark; Martinello, Marianne; Gilliver, Rosie; Marks, Philippa; Applegate, Tanya L.; Dore, Gregory J.; et al.
Abstract: Background and Aims: Direct‐acting antiviral therapy for hepatitis C virus (HCV) is effective, but few prospective studies among people with ongoing injecting drug use exist. This study evaluated the efficacy of elbasvir/grazoprevir in people with HCV genotype 1/4 (G1/4) infection and recent injecting drug use. An exploratory aim evaluated the feasibility of fingerstick point‐of‐care HCV RNA testing prior to and following treatment. Methods: DARLO‐C (ClinicalTrials.gov : NCT02940691) is an open‐label phase 4 trial. Participants were recruited between May 2017 and March 2018 from two drug treatment clinics, two hospital clinics, and one community clinic in Australia. Inclusion criteria included recent injection drug use (previous 6 months) and HCV G1/4 infection. Exclusion criteria included prior HCV treatment and decompensated liver disease. Participants received elbasvir/grazoprevir once‐daily for 12 weeks. The primary endpoint was undetectable HCV RNA 12 weeks post‐treatment (SVR). Fingerstick whole‐blood samples were tested using the Xpert HCV Viral Load Fingerstick (Xpert HCV VL Fingerstick) assay and compared to the Aptima HCV Quant Dx Assay on plasma samples. Results: Of a planned 150 participants, 32 were enrolled due to slower than anticipated recruitment [median age 46 years, 10 (31%) female, 29 (91%) G1a]. Eighteen (56%) were receiving opioid agonist therapy and 29 (91%) injected in the previous month. Twenty‐six (81%) of 32 completed treatment (lost to follow‐up, n = 5; incarceration, n = 1). There were no virological failures. Twenty‐four (75%, 95% CI 59%‐91%) of 32 achieved SVR. Two participants who completed treatment did not have SVR (loss to follow‐up, n = 1; refused test, n = 1). Among paired samples (n = 36), sensitivity of the Xpert HCV VL Fingerstick assay for HCV RNA detection was 100.0% (95% CI 75.3%‐100.0%) and specificity was 95.7% (95% CI 78.1%‐99.9%). Conclusion: Elbasvir/grazoprevir is effective among people with HCV G1 with recent injecting drug use. Implementation of point‐of‐care HCV RNA testing was feasible, but the high error rate requires investigation.